1998
DOI: 10.1021/ja9814319
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Diastereomeric Nickel(II)N-Glycoside Complexes Using Tandem Mass Spectrometry

Abstract: Ni(II) N-glycoside complexes of four diastereomeric monosaccharides were synthesized and analyzed by fast atom bombardment-mass spectrometry. The average kinetic energy release (KER) associated with the formation of a C 2 H 4 O 2 neutral loss was indicative of stereochemical differences in the coordinated monosaccharide. Isotopic labeling studies and various linked scanning techniques were undertaken, suggesting multiple dissociation pathways from different reacting configurations, leading to the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 57 publications
6
41
0
Order By: Relevance
“…All Zn-coordinating bond lengths were between 1.98 -2.19 Å. The monosaccharide ring conformation was found to occupy the 4 C 1 conformation, which was previously observed in theoretical calculations of Ni(II)/diaminopropane/glucose complexes [32]. Structure Glc7 exhibited a theoretical cross section of 100.0 Å 2 which deviates 1.2% from the experimental cross section.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…All Zn-coordinating bond lengths were between 1.98 -2.19 Å. The monosaccharide ring conformation was found to occupy the 4 C 1 conformation, which was previously observed in theoretical calculations of Ni(II)/diaminopropane/glucose complexes [32]. Structure Glc7 exhibited a theoretical cross section of 100.0 Å 2 which deviates 1.2% from the experimental cross section.…”
Section: Resultssupporting
confidence: 60%
“…Previous studies have shown that synthesis of N-glycosides of this type yield specifically the beta-anomer [36]. While the 4 C 1 conformation is known to be the lowest energy conformation of monosaccharides [37], previous DFT calculations of these complexes observed twist boat geometries as well [32]. A total of 29 initial geometries were generated allowing the coordination of the metal center to each m/z 364 3 328…”
Section: Resultsmentioning
confidence: 99%
“…and mannose isotopologues revealed that the C 2 H 4 O 2 loss indeed is a superposition of two different cross-ring cleavages that involve either C-5 and C-6 or C-4 and C-5 (Smith & Leary, 1998). Several different mechanism can account for the observed fragmentations (Scheme 11).…”
Section: Molecular Recognition and Supramolecular Chemistrymentioning
confidence: 99%
“…To date, the vast majority of ion-molecule interaction studies performed by mass spectrometry focus on positive ion studies of cationic adduct species, especially protonated molecules [14] and alkali metal adducts [18 -21]. Dication adduct species, such as alkaline earth metal [22] and transition metal [23] adducts of oligosaccharides have also been explored. Small inorganic anions attaching to neutral analyte molecules, on the other hand, have received far less research attention.…”
mentioning
confidence: 99%